Preleukemic Hematopoietic Stem Cells in Human Acute Myeloid Leukemia - Corces, M. Ryan; Chang, Howard Y.; Majeti, Ravindra (Frontiers in Oncology, 2017)
Acute myeloid leukemia (AML) is an aggressive malignancy of the bone marrow characterized by an uncontrolled proliferation of undifferentiated myeloid lineage cells. Decades of research have demonstrated that AML evolves from the sequential acquisition of genetic alterations within a single lineage of hematopoietic cells. More recently, the advent of high-throughput sequencing has enabled the identification of a pre-malignant phase of AML termed pre-leukemia. Multiple studies have demonstrated that AML can arise from the accumulation of mutations within hematopoietic stem cells (HSCs). These HSCs have been termed “pre-leukemic HSCs” as they represent the evolutionary ancestors of the leukemia. Through examination of the biological and clinical characteristics of these pre-leukemic HSCs, this review aims to shed light on some of the unexplored questions in the field. We note that some of the material discussed is speculative in nature and is presented in order to motivate future work.